Levels of Evidence in Plastic Surgery Research: A 10-Year Bibliometric Analysis of 18, 889 Publications From 4 Major Journals. (26th June 2019) - Rifkin, William J; Yang, Jenny H; DeMitchell-Rodriguez, Evellyn; Kantar, Rami S; Diaz-Siso, J Rodrigo; Rodriguez, Eduardo D
Abstract: Background: Improving the quality of research published in plastic surgery literature has been recognized as a difficult and time-intensive process. Despite significant progress over the last decade, leaders in the field continue to advocate for higher-quality studies to better inform clinical practice. Objectives: The aim of this study was to evaluate and analyze trends in the levels of evidence (LOEs) of the plastic surgery literature over the last decade in 4 major journals. Methods: After systematic review of all articles published between 2008 and 2017 in Plastic and Reconstructive Surgery, Annals of Plastic Surgery, Journal of Plastic, Reconstructive, and Aesthetic Surgery, and Aesthetic Surgery Journal ( ASJ ), included articles were assigned an LOE and classified according to study design and category. Results: In total, 8211 articles were included. Case series and reports represented 36.1% and 13.6% of studies, respectively. Additionally, 27.2% were retrospective cohort studies, 8.2% prospective cohort studies, 3.9% systematic reviews, and 2.9% randomized controlled trials (RCTs). Overall, the percentage of Level I/II studies has increased from 10.9% in 2008 to 17.3% in 2017. ASJ published the greatest proportion of Level I/II studies (23.2%) and RCTs (5.1%) of all the journals. There were significant differences in the distribution of Level I/II studies by journal ( P < 0.001) and category ( P < 0.001). Conclusions: Over the past decade, plastic surgery journals have published higher-quality research and a significantly greater proportion of Level I and II studies. The field must continue to strive for robust study designs, while also recognizing the importance of lower-LOE research.